Gut microbiota — bidirectional modulator: role in inflammatory bowel disease and colorectal cancer - Cui, Xilun; Li, Changfeng; Zhong, Jing; Liu, Yuanda; Xiao, Pengtuo; Liu, Chang; Zhao, Mengwei; Yang, Wei (Frontiers in Immunology, 2025)
The gut microbiota is a diverse ecosystem that significantly impacts human health and disease. This article focuses on how the gut microbiota interacts with inflammatory bowel diseases and colorectal tumors, especially through immune regulation. The gut microbiota plays a role in immune system development and regulation, while the body’s immune status can also affect the composition of the microbiota. These microorganisms exert pathogenic effects or correct disease states in gastrointestinal diseases through the actions of toxins and secretions, inhibition of immune responses, DNA damage, regulation of gene expression, and protein synthesis. The microbiota and its metabolites are essential in the development and progression of inflammatory bowel diseases and colorectal tumors. The complexity and bidirectionality of this connection with tumors and inflammation might render it a new therapeutic target. Hence, we explore therapeutic strategies for the gut microbiota, highlighting the potential of probiotics and fecal microbiota transplantation to restore or adjust the microbial community. Additionally, we address the challenges and future research directions in this area concerning inflammatory bowel diseases and colorectal tumors.